Fluoretação de águas de abastecimento público: iniquidades e impacto sobre a cárie dentária - Schmitt, Ernesto Josué (2020)
Fluoridation of public water supplies has been considered an important measure to minimize inequities in oral health. In this Thesis, possible associations between Brazilian macro-regions, population size, Human Development Index at Municipal level (HDI-M) and access to piped water, with fluoridation and dental caries at 12 years-old outcomes were investigated. An article with an ecological design was prepared, using public secondary data bases: national epidemiological surveys carried out in 2003 and in 2010, and Atlas of Human Development in Brazil, for the years 2000 and 2010. The 50 municipalities that participated in the two epidemiological studies that, after adjustments, generated a total of 57,388 inhabitants. The first analysis, using data from SB Brasil 2003, had fluoridation as a dependent variable, categorized as: before 1990, after 1990 or absent; the independent ones were the country's macro-region - North, Northeast, Midwest, Southeast and South); population size for the year 2000, categorized according to the number of inhabitants in 2000: up to 20,000, from 20,001 to 50,000, 50,001 to 150,000, and ≥ 150,000; HDI-M for the year 2000, categorized as low (<0.600), medium (0.600 - 0.699) and high (> 0.699); and access to piped water dichotomized as “with” or “without” in 2000. For the SB Brasil 2010 data, the fluoridation cutoff year was 2004; population size, HDI-M and piped water were changed for 2010. With the outcome of dental caries, the same was followed with the independent variables. The Chi-Square test adjusted by the Bonferroni method was applied to determine the association between the explanatory variables and their ability to predict the outcomes of interest. As a result, there was a statistically significant difference between the country's macro-regions and the presence or absence of fluoridation (p <0.001), with marked inequality, where in the Northeast the nonexistence of the measure exceeded 80.0% and had no improvement from 2003 to 2010; conversely, South and Southeast has coverage of 100.0%. For the years 2003 and 2010, the fluoridation variable was statistically significantly associated with all explanatory variables, with a value of p <0.001. North and Northeast, in both years, comprised more people who do not have access to the measure. As for population size, the category “≥ 150,001 inhabitants” coincided with early access to water fluoridation, either “until 1990” or “until 2004”. For the HDI-M, with data from 2003, it was found that in the “low” category, the association with the absence of fluoridation prevailed. For 2010, it was also highlighted that the best development was associated with the implementation of the measure. Still, for 2003 and 2010 it was clear to reduce the percentage of people living in regions without fluoridation, even through the encouragement of the health policy of 2004, and this occurs regardless of the HDI-M extract. As for access to piped water, the same behavior was identified, that is, those who do not receive piped water, do not have fluoridation. Regarding the outcome of dental caries, in general, DMFT ≥ 1 increased in all regions in the present sample. In 2003 and 2010, this experience was greater in the population of the North and Northeast regions. DMFT ≥ 1, in both years, was associated with population size, except for “≥ 150,001 inhabitants”, in which DMFT = 0 was higher. In 2010, within each population size range, when comparing caries experience, those in the “with” category had values more than double when compared to the “without” category, in all extracts. As for the HDI-M, in 2010, the association with caries experience was not statistically significant (p = 0.066). However, for the least developed (HDI-M <0.600), there was more experience of caries (DMFT ≥ 1), in the years 2003 and 2010. The fact of having access to piped water or not was not associated with the experience of caries in 2003 (p = 0.061), and in 2010 a higher prevalence of individuals who have access to piped water was classified in the DMFT = 0 category. Finally, in the association between dental caries and water fluoridation, the impact was clear that the measure has on the disease, with a significant association for both years (p <0.001). In 2003, the earliest fluoridation (before 1990) pointed to an increase in the number of individuals with DMFT = 0. In terms of the time frame of 2004 fluoridation, a higher frequency of the disease was also observed when there was no fluoridation. It can be concluded that both water fluoridation and dental caries are related to other factors analyzed in the present sample, such as the country's macroregion, population size, HDI-M and access to piped water. It should also be considered that fluoridation is an important measure for reducing the prevalence and severity of caries disease, with the ability to reduce inequities in oral health.